Formulation and Antioxidant Activity of Liquid Soap Containing Soursop (Annona muricata L.) Leaf and Soybean (Glycine max (L.) Merr.) Seed Extracts by DPPH Assay - Hari Purwani, Asih Imulda Asih; Pramasari, Nadia; Lailiyah, Munifatul (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2025)
Skin aging is driven by intrinsic and extrinsic factors, with oxidative stress as the main mechanism of extrinsic aging. Natural antioxidants, such as soursop (Annona muricata L.) leaves and soybean (Glycine max (L.) Merr.) seed coats, may serve as alternatives to synthetic antioxidants for skin protection. This study aimed to formulate liquid soap containing extracts of soursop leaves and soybean seed coats, and to evaluate its physicochemical properties and antioxidant activity. Three formulations (F1, F2, F3) with different soybean extract concentrations (0.25%, 0.5%, 1%) were tested for organoleptic properties, pH, foam height, spreadability, homogeneity, and quercetin content using TLC-densitometry. Results showed that F1 had good physical properties, including homogeneity, spreadability (5–7 cm), and suitable pH (9–10). Antioxidant activity was weak in all formulations (IC₅₀ > 250 µg/mL), likely due to low extract levels and soap matrix interactions. TLC-densitometry confirmed the presence of quercetin with an average content of 55.73 ppm (0.189% w/w). In conclusion, the formulated liquid soap demonstrated good physicochemical quality but limited antioxidant activity, indicating the need for further optimization while showing the potential of local herbal ingredients for functional cosmetic development.